Adult derived genetic blood pressure scores and blood pressure measured in different body postures in young children. (29th August 2020) - Jansen, Maria AC; Dalmeijer, Geertje W; Visseren, Frank LJ; van der Ent, Cornelis K; Leusink, Maarten; Onland-Moret, N Charlotte; Maitland-van der Zee, Anke H; Grobbee, Diederick E; Uiterwaal, Cuno SPM
Abstract: Aims: Several genes are related to blood pressure (BP) levels in adults, but it is largely unknown whether these genes also determine BP early in life. Methods: Systolic BP (SBP) and diastolic BP (DBP) were measured in 720 5-year-old children from the WHeezing-Illnesses-STudy-LEidsche-Rijn (WHISTLER) birth cohort in sitting and supine positions using a semi-automatic oscillometric device. Illumina chip technology was used to genotype 18, 19, 11 and 12 single nucleotide polymorphisms associated with adult SBP, DBP, mean arterial pressure (MAP) and hypertension, respectively, in the children's DNA and separate weighted genetic risk scores (GRSs) were constructed. The associations are reported as linear regression coefficients (mmHg BP in childhood/GRS score point) or odds ratios (highest childhood BP quintile/hypertension GRS score point). Results: A higher GRS for SBP was related to higher supine SBP (0.37, 95% CI 0.01 to 0.7), but not to supine DBP (−0.05, 95% CI −0.4 to 0.3) or supine MAP (0.19, 95% CI −0.1 to 0.5). A higher GRS for DBP was related to a higher supine SBP (0.66, 95% CI 0.1 to 1.2), but not to supine DBP (−0.07, 95% CI −0.6 to 0.4) or supine MAP (0.28, 95% CI −0.2 to 0.7). With the sitting BP measurements, the GRSs for SBP and DBP were related to neither SBP nor DBP. No association was found between GRS for MAP and SBP, DBP or MAP. Hypertension GRS was not associated with a higher BP in children. Conclusions: Higher scores for adult derived diastolic and systolic BP genes appear to be related to higher supine systolic BP at age 5 years.